ANALISIS PELAKSANAAN REKRUTMEN DAN SELEKSI CALON KARYAWAN BARU DI RSIA KENDANGSARI MERR SURABAYA - Anis Fitri Aulia (Fakultas Kesehatan Universitas Nahdlatul Ulama Surabaya, 2019)
Recruitment and selection are the most important part in the formation of quality human resources. The effectiveness of recruitment and selection will determine the success of employee performance in the future. The aim of this study was to learn the implementation of recruitment and selection of prospective employees at RSIA Kendangsari Merr Surabaya. The method of this study is observational by using qualitative data in the form of primary data and secondary data. The results of this study found that the recruitment method in RSIA Kendangsari Merr consists of promotion, rotation, job posting, advertising, websites, employee recommendations, labor department, labor placement agencies, and job training programs. While the selection process in RSIA Kendangsari Merr consists of administrative selection, written tests, interview tests, psychological tests, credentials, health checks, and work agreements for a 3-month trial period. The conclusion of this study that all recruitment methods in RSIA Kendangsari Merr Surabaya are in accordance with the internal and external methods of recruitment methods, and the selection process is in accordance with the rules of the selection stages. Recommendation for RSIA Kendangsari Merr is to provide additional recruitment method, it is job bidding. Job bidding can be applied at RSIA Kendangsari Merr Surabaya by offering job positions to employees who are competent with career development to meet certain specifications required. Besides being beneficial for motivation and career development of HR, it also minimizes the costs of recruitment and selection sourced from external organizations.